PENGARUH KINERJA KEUANGAN TERHADAP NILAI PERUSAHAANDENGAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAI VARIABEL PEMODERASI - Dhian Andanarini Minar Savitri (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2017)
Company value described how good or bad the manager of wealth management, itcan be seen from the measurement of financial performance obtained. The purpose of thisreasearch is to analyze the effect of the financial performance of the company's value tothe disclosure of corporate social responsibility as a moderating variable onmanufacturing companies listed in Indonesia Stock Exchange period 2012-2015. Theindependent variables are financial performance (ROA, ROE, CR, DER, TATO), thedependent variable is the enterprise value (Tobin's Q) and variable CSR as moderation.Samples were 30 companies listed on the Stock Exchange. Sampling of thepopulation using purposive sampling technique. Financial reporting data, ICMD andannual reports obtained from IDX. Testing the hypothesis in this research using multipleregression analysis with SPSS applications 21.The results of the research with multiple linear regression showed that theROA, ROE, CR, DER significant positive effect on firm value, while TATO significantnegative effect on firm value.The moderating variables with interaction test shows thatdisclosure corporate social responsibility moderating influence ROA by value company,while corporate social responsibility disclosure doesn’t moderating influence ROE, CR,DER, TATO by value of the firm.